A Coupled One-Dimensional Numerical Simulation of the Land Subsidence Process in a Multilayer Aquifer System due to Hydraulic Head Variation in the Pumped Layer. (23rd January 2018) - Wang, Ye; Zhang, Mao-sheng; Hu, Fu-sheng; Dong, Ying; Yu, Kun
Abstract : After exploitation of groundwater had been reduced and the groundwater level of the confined aquifer had risen, land subsidence was observed to continue rather than cease for several years according to the layer-wise mark monitoring data in Xi'an. To analyze the phenomena, a numerical model of a coupled one-dimensional multilayer aquifer system is developed to represent land subsidence due to hydraulic head variation in the pumped layer. The numerical simulation results show that the pressure head in other layers does not rise immediately when the hydraulic head in the pumped layer starts to recover after pumping ceases. In addition, after the pumping is stopped, a dividing point can be found in aquitards next to the pumped layer, with the aquitards being divided into two parts: a compressed part and a rebounding part. The dividing points move toward the side and away from the pumped layer with the transferring of pore pressure in the aquitard. The results of the simulation also show that there is a transition period between land subsidence and rebound. In this transition period, land could continue to subside even though the hydraulic head in the pumped layer begins to recover.